Modyfikacja kary w postępowaniu wykonawczym - Wiciński, Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
According to the Corrections Code, execution of penalty or penal measure is subject to fulfillment of corrective and preventive goals. Since the 18th century, progressive tendencies regarding imprisonment indicated the need to corrective influence — motivating the perpetrator to exhibit socially-acceptable behavior in order to prevent his relapse into crime. The system of execution of deprivation of liberty imprisonment is called a system of slow progression, which means that the penalty can be modified in case of progress in social adaptation or lack of such. The modification process is related to many procedures during execution of penalty. Based on diverse character of such procedures, one can classify them as incidental or autonomous, the latter leading to modification of penalty, e.g. external or internal, permanent, episodic, conditional or unconditional and others, all of which optimize the possibility of fulfillment of the primary goal of the penalty, that is preventing of relapse into crime.
Keywords: kodeks karny; sąd penitencjarny; pozbawienie wolności; ograniczenie wolności; grzywna; środki karne; system dozoru elektronicznego; progresywny system wykonywania kary pozbawienia wolności; postępowania incydentalne; autonomiczne postępowanie; modyfikacja kary